Body mass index change in gastrointestinal cancer and chronic obstructive pulmonary disease is associated with Dedicator of Cytokinesis 1. Issue 3 (2nd January 2017) - McDonald, Merry‐Lynn Noelle; Won, Sungho; Mattheisen, Manuel; Castaldi, Peter J.; Cho, Michael H.; Rutten, Erica; Hardin, Megan; Yip, Wai‐Ki; Rennard, Stephen I.; Lomas, David A.; Wouters, Emiel F.M.; Agusti, Alvar; et al.
Abstract: Background: There have been a number of candidate gene association studies of cancer cachexia‐related traits, but no genome‐wide association study (GWAS) has been published to date. Cachexia presents in patients with a number of complex traits, including both cancer and COPD. The objective of the current investigation was to search for a shared genetic aetiology for change in body mass index (ΔBMI) among cancer and COPD by using GWAS data in the Framingham Heart Study. Methods: A linear mixed effects model accounting for age, sex, and change in smoking status was used to calculate ΔBMI in participants over 40 years of age with three consecutive BMI time points ( n  = 4162). Four GWAS of ΔBMI using generalized estimating equations were performed among 1085 participants with a cancer diagnosis, 204 with gastrointestinal (GI) cancer, 112 with lung cancer, and 237 with COPD to test for association with 418 365 single‐nucleotide polymorphisms (SNPs). Results: Two SNPs reached a level of genome‐wide significance ( P  < 5 × 10 −8 ) with ΔBMI: (i) rs41526344 within the CNTN4 gene, among COPD cases ( β  = 0.13, P  = 4.3 × 10 −8 ); and (ii) rs4751240 in the gene Dedicator of Cytokinesis 1 ( DOCK1 ) among GI cancer cases ( β  = 0.10, P  = 1.9 × 10 −8 ). The DOCK1 SNP association replicated in the ΔBMI GWAS among COPD cases ( β meta‐analyis  = 0.10, P meta‐analyis  = 9.3 × 10 −10 ). The DOCK1 gene codes for the dedicator of cytokinesis 1 protein, which has a role in myoblast fusion. Conclusions: In sum, one statistically significant common variant in the DOCK1 gene was associated with ΔBMI in GI cancer and COPD cases providing support for at least partially shared aetiology of ΔBMI in complex diseases.